ANALISIS KARAKTER PESERTA DIDIK DALAM PEMBELAJARAN TATAP MUKA TERBATAS DI SEKOLAH DASAR - Annisa Qomariah Nisa (SISTEMA: Jurnal Pendidikan, 2022)
Character education in face-to-face learning is limited to what must be prepared because the teacher is in the learning process and the meeting is very short. The purpose of this study is to analyze the characters that occur in PTMT on IPS loads . the method used in this research is qualitative. By using purposive sampling technique. Data collection techniques using structured observation methods, interviews used are semi-structured interviews and documentation. Data analysis used to collect data, data reduction, data presentation, and drawing conclusions. Checking the data using source trangulation. The results in the study illustrate that the characters formed are disciplined, independent and responsible. Therefore, independent discipline and important responsibility during the learning process can have an impact on the behavior of students inside and outside the classroom. Character education in elementary schools does not add right and wrong to students. However, it must be able to instill good habits, so that participants feel they understand, feel and do these good things. Forming the character of shared responsibility with the government, community, parents and teachers, which requires balanced cooperation. Keywords: Character, Limited Face-to-face Learning (PTMT), Elementary School